2019
DOI: 10.1016/j.ijrobp.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Patient-Reported Dry Eye Syndrome After Whole Brain Radiation

Abstract: Purpose-Dry eye is not typically considered a toxicity of whole brain radiation (WBRT). We analyzed dry eye syndrome as part of a prospective study of patient-reported outcomes after WBRT.Methods-Patients receiving WBRT to 25-40 Gy were enrolled on a study with dry mouth as the primary endpoint and dry eye syndrome as a secondary endpoint. Patients received 3-dimensional WBRT using opposed lateral fields. Per standard practice, lacrimal glands were not prospectively delineated. Patients completed the Subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In the recent prospective study, 46% of patients experienced dry eye symptoms one month after radiotherapy. These symptoms can begin immediately after therapy and be sustained for up to six months [3]. Dry eye syndrome after radiotherapy results not only in acute discomfort, but also in chronic disease during the patient’s remaining years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent prospective study, 46% of patients experienced dry eye symptoms one month after radiotherapy. These symptoms can begin immediately after therapy and be sustained for up to six months [3]. Dry eye syndrome after radiotherapy results not only in acute discomfort, but also in chronic disease during the patient’s remaining years.…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation causes damage in normal tissues located in the field of radiation and induces both functional and morphological changes in glandular tissues, including the salivary gland, thryroid gland, and lacrimal gland (LG) [1,2,3]. Dry eye syndrome is relatively common as a symptom of dose-/volume-dependent acute and late toxicity after radiotherapy [3,4,5,6], the significance of which has been overlooked due to its apparent harmlessness. However, the patients experience complications in daily tasks, such as constant irritation and blurred vision [7], which may in turn lead to psychotic complications [8].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of patients with an increase in dry eye symptoms was significantly higher at 1 month (≥1 point Subjective Evaluation of Symptom of Dryness increase) for lacrimal V20Gy at least 79% was 46% while less than 79% associated with 15% ( P = .02). 66 Importantly, this appears to be a previously over-looked toxicity to WBRT. However, care should be taken in attempting to spare the lacrimal glands as this toxicity measure is not validated and modifications in the field to spare lacrimal glands may compromise dose to the cribriform plate although this may be possible with HA-WBRT.…”
Section: Radiotherapymentioning
confidence: 99%
“…Whole brain radiation (WBRT) is a common treatment for patients with brain metastases [ 1 6 ]. Many patients who receive WBRT have a poor prognosis, and it is important to minimize both acute and late toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…More-recently, in a prospective study, we reported that patients receiving standard WBRT (without prospective delineation of the parotid or lacrimal glands) resulted in clinically-significant acute xerostomia and dry eye in roughly 35% and 25% of cases, respectively with toxicity rates associated with glandular doses [ 1 , 10 ]. In those reports, a summary of the reported toxicities was provided together with a statistical analysis of their correlation against given dose volume metrics.…”
Section: Introductionmentioning
confidence: 99%